2014
DOI: 10.1161/strokeaha.114.006617
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glymphatic Perfusion After Strokes Revealed by Contrast-Enhanced MRI

Abstract: Background and Purpose— The aim of the present study was to investigate the impact of different stroke subtypes on the glymphatic system using MRI. Methods— We first improved and characterized an in vivo protocol to measure the perfusion of the glymphatic system using MRI after minimally invasive injection of a gadolinium chelate within the cisterna magna. Then, the integrity of the glymphatic system was evaluated in 4 stroke models in mice including su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
342
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 350 publications
(368 citation statements)
references
References 10 publications
19
342
2
5
Order By: Relevance
“…This dislocation is similar to the changes found in the aging brain [10]. Impairment of the function of the glymphatic system is also noted after embolic ischemic stroke, however, this damage is transient [18]. Thus, different brain injuries like stroke, subarachnoid bleeding and repetitive traumatic events impair the function of the glymphatic system [1].…”
Section: Arc Journal Of Neuroscience Page|18supporting
confidence: 56%
“…This dislocation is similar to the changes found in the aging brain [10]. Impairment of the function of the glymphatic system is also noted after embolic ischemic stroke, however, this damage is transient [18]. Thus, different brain injuries like stroke, subarachnoid bleeding and repetitive traumatic events impair the function of the glymphatic system [1].…”
Section: Arc Journal Of Neuroscience Page|18supporting
confidence: 56%
“…Interestingly, pretreating young wild-type mice with Aβ suppressed glymphatic influx, suggesting that not only is Aβ aggregation a consequence of a breakdown of flow within this pathway, but it may also be an independent cause of glymphatic dysfunction (23). Further, glymphatic impairment is a prominent feature of cerebrovascular disease, including both subarachnoid hemorrhage and multiple microinfarction (24,25). Following traumatic brain injury, reduced clearance of cortical interstitial solute was associated with motor and cognitive neurological deficits (26).…”
Section: The Glymphatic System: Anatomy and Function In Health And DImentioning
confidence: 99%
“…4 We recently demonstrated that this system is severely impaired after SAH, but not after ICH, and may trigger toxic metabolite accumulation within the brain parenchyma. 5 Interestingly, we showed in an experimental SAH model that IVF restores the function of the glymphatic system. Therefore, in addition to macroscopic clot removal, IVF may restore glymphatic circulation in patients presenting IVH secondary to SAH.…”
Section: To the Editormentioning
confidence: 91%